Pengaruh Kepemilikan Manejerial, Dewan Komisaris Independent Dan Komite Audit Terhadap Return On Asset Perbankan Syariah Yang Terdaftar Di Bursa Efek Indonesia Tahun 2018-2022 - Kurniawati Syawalinda; Usdeldi Usdeldi; Ahmad Syahrizal (STIKes Ibnu Sina Ajibarang, 2023)
This research was conducted with the aim of examining the effect of good corporate governance on the financial performance of Islamic banking listed on the Indonesian stock exchange in 2018-2022. This study was tested using 3 independent variables, namely: managerial ownership, independent board of commissioners and audit committee. For the dependent variable, namely Return On Assets. The population used in this research is Islamic banking companies on the Indonesia Stock Exchange in 2018-2022. The samples used in this study amounted to 45 samples. The analysis used in this study was multiple linear analysis and was assisted by SPSS Version 22. The data used were secondary data. The results of this study indicate that Managerial Ownership has no significant effect on Return On Assets (ROA). This can be proven by the results of the t-count value of 1.482 < t-table of 2.020 and a significant value of 0.632 > 0.05, the independent board of commissioners shows that there is a significant influence on Return On Assets (ROA). This can be proven by the results of the t count value of 3.397 > t table 2.020 and a significant value of 0.003 <0.05. The Audit Committee shows that there is a significant influence on Return On Assets (ROA). This can be proven by the results of the t count value of 2.942 > t table of 2.020 and the sig value of 0.019 <0.05. Managerial ownership, independent board of commissioners, and audit committee simultaneously or jointly have a significant effect on Return On Assets (ROA). It is known that the significance value for managerial ownership, independent board of commissioners, and audit committee (X) simultaneously on Return On Asset (ROA) of 0.006 <0.05 and the value of f count > f table (5.259 > 3.02).